AWARENESS OF ADVERSE EFFECTS OF AZATHIOPRINE AMONG PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (8th June 2013) - Spence, A D; Lee, R; Keegan, D; Doherty, G A; Mulcahy, H; O'Donoghue, D; Murphy, S J
Abstract : Introduction: Azathioprine, an important immunomodulator in the management of Inflammatory Bowel Disease (IBD), has potential serious side-effects about which patients should have awareness. Aims/Background: The aim was to assess understanding of side-effects of azathioprine in patients with IBD. Method: A 10-question survey was completed anonymously by IBD patients attending St. Vincent's Hospital, Dublin. Information received prior to treatment, side-effect awareness and blood monitoring data were collated. Results: 96 patients completed questionnaires (52% male, 48% female). Fifty-nine (61%) patients had Crohn's disease, 33 (34%) ulcerative colitis, and 4 indeterminate colitis. Sixty-two (65%) received information about azathioprine from their physician (23% written, 37% verbal, 39% written and verbal). 83 (93%) patients took their medication daily. 61 (71%) were aware of the complication of low WBC count. Eighty-nine (93%) had blood monitoring, but frequency varied. Awareness of other side-effects was lower (38% skin rash, 30% pancreatitis, and 36% lymphoma). Thirty-eight (40%) patients had felt unwell while taking azathioprine. 34% of patients who had felt unwell on azathioprine visited their GP; only one-third had blood tests. Conclusion: Although compliance with azathioprine was high, only 65% of patients recalled receiving information on azathioprine side-effects. Most patients had monitoring for neutropenia, but frequency varied. Awareness of important side-effects (lymphoma) was low. These findings emphasize the importance of reminding patients of the side-effects of azathioprine, and blood monitoring. The use of smart phones with 'apps', in these young patients, may be helpful as reminders of adverse effects and blood monitoring.